Exercícios de resistência para a promoção de saúde de grupos especiais de coronariopatas - Oliveira, Janine Leite Moura de (2008)
Introduction. Among the most important issue of public health, nowadays, is the development of strategies for the promotion of health of patients with cardiovascular disease. For many decades, the coronary artery disease has prevailed as the main cause of mortality and one of the most frequent cause of incapacity in Brazil and the world. The practice of physical exercises is indicated to promote the health of patients with coronary artery disease. After an intense cardiac event in patient with coronary artery disease, resistance exercises have been suggested because they promote a significant strengthening of the peripheral cardiac muscle. But the benefits and risks of those exercises have not been clarified yet and so, the professionals of physical rehabilitation need more scientific evidence for its application in clinical practice. Objectives: To search for and evaluate the evidence related to the benefits and risks of resistance exercises for coronary patients after a myocardial infarction (MI) and coronary artery bypass. Method: An integrative review of the literature was made. The question established was: What is the evidence of benefits and risks related to resistance exercise for patients after a myocardial infarction (MI) and coronary artery bypass? The criteria for including the studies consisted of randomized controlled trials considering the research question. We searched all primary studies since 1977, in the following electronic data bases: Medline, PEDro, Cochrane Controlled Trials Database and CINAHL. Results: After the selecting process, 11 articles were included in the review. Five articles presented just the resistance exercises and 6 combined the resistance exercises with aerobic exercise. The evidences related to the benefits of intervention found in the articles were the improvement of peripheral muscular strength, increase of physical capacity, improvement of emotional state and the quality of life. No risks were reported in the articles related the application of the resistance exercise. Conclusions: the resistance exercises can be used as a safe and effective strategy in programs of health promotion of coronary patients, making possible the social, physical and psychological rehabilitation of those individuals. Key words: health promotion, coronary patients, resistance exercises, integrative review